HYPK coordinates degradation of polyneddylated proteins by autophagy. Issue 8 (3rd August 2022) - Ghosh, Debasish Kumar; Ranjan, Akash
ABSTRACT: Selective degradation of protein aggregates by macroautophagy/autophagy is an essential homeostatic process of safeguarding cells from the effects of proteotoxicity. Among the ubiquitin-like proteins, NEDD8 conjugation to misfolded proteins is prominent in stress-induced protein aggregates, albeit the function of neddylation in autophagy is unclear. Here, we report that polyneddylation functions as a post-translational modification for autophagic degradation of proteotoxic-stress induced protein aggregates. We also show that HYPK functions as an autophagy receptor in the polyneddylation-dependent aggrephagy. The scaffolding function of HYPK is facilitated by its C-terminal ubiquitin-associated domain and N-terminal tyrosine-type LC3-interacting region which bind to NEDD8 and LC3 respectively. Both NEDD8 and HYPK are positive modulators of basal and proteotoxicity-induced autophagy, leading to protection of cells from protein aggregates, such as aggregates of mutant HTT exon 1. Thus, we propose an indispensable and additive role of neddylation and HYPK in clearance of protein aggregates by autophagy, resulting in cytoprotective effect during proteotoxic stress. Abbreviations: ATG5, autophagy related 5; ATG12, autophagy related 12; ATG14, autophagy related 14; BECN1, beclin 1; CBL, casitas B-lineage lymphoma; CBLB, Cbl proto-oncogene B; GABARAP, GABA type A receptor-associated protein; GABARAPL1, GABA type A receptor associated protein like 1; GABARAPL2, GABA type A receptor associated protein like 2; GFP, green fluorescent protein; HTT, huntingtin; HTT97Q exon 1, huntingtin 97-glutamine exon 1; HUWE1, HECT, UBA and WWE domain containing E3 ubiquitin protein ligase 1; HYPK, huntingtin interacting protein K; IgG, immunoglobulin G; IMR-32, Institute for Medical Research-32; KD, knockdown; Kd, dissociation constant; LAMP1, lysosomal associated membrane protein 1; LIR, LC3 interacting region; MAP1LC3/LC3, microtubule associated protein 1 light chain 3; MAP1LC3A/LC3A, microtubule associated protein 1 light chain 3 alpha; MAP1LC3B/LC3B, microtubule associated protein 1 light chain 3 beta; MARK1, microtubule affinity regulating kinase 1; MARK2, microtubule affinity regulating kinase 2; MARK3, microtubule affinity regulating kinase 3; MARK4, microtubule affinity regulating kinase 4; MCF7, Michigan Cancer Foundation-7; MTOR, mechanistic target of rapamycin kinase; NAE1, NEDD8 activating enzyme E1 subunit 1; NBR1, NBR1 autophagy cargo receptor; NEDD8, NEDD8 ubiquitin like modifier; Ni-NTA, nickel-nitrilotriacetic acid; NUB1, negative regulator of ubiquitin like proteins 1; PIK3C3, phosphatidylinositol 3-kinase catalytic subunit type 3; PolyQ, poly-glutamine; PSMD8, proteasome 26S subunit, non-ATPase 8; RAD23A, RAD23 homolog A, nucleotide excision repair protein; RAD23B, RAD23 homolog B, nucleotide excision repair protein; RFP, red fluorescent protein; RPS27A, ribosomal protein S27a; RSC1A1, regulator of solute carriers 1; SNCA, synuclein alpha; SIK1, salt inducible kinase 1; siRNA, small interfering ribonucleic acid; SOD1, superoxide dismutase 1; SPR, surface plasmon resonance; SQSTM1, sequestosome 1; SUMO1, small ubiquitin like modifier 1; TAX1BP1, Tax1 binding protein 1; TDRD3, tudor domain containing 3; TNRC6C, trinucleotide repeat containing adaptor 6C; TOLLIP, toll interacting protein; TUBA, tubulin alpha; TUBB, tubulin beta class I; UBA, ubiquitin-associated; UBA1, ubiquitin like modifier activating enzyme 1; UBA5, ubiquitin like modifier activating enzyme 5; UBAC1, UBA domain containing 1; UBAC2, UBA domain containing 2; UBAP1, ubiquitin associated protein 1; UBAP2, ubiquitin associated protein 2; UBASH3B, ubiquitin associated and SH3 domain containing B; UBD/FAT10, ubiquitin D; UBE2K, ubiquitin conjugating enzyme E2 K; UBLs, ubiquitin-like proteins; UBL7, ubiquitin like 7; UBQLN1, ubiquilin 1; UBQLN2, ubiquilin 2; UBQLN3, ubiquilin 3; UBQLN4, ubiquilin 4; UBXN1, UBX domain protein 1; ULK1, unc-51 like autophagy activating kinase 1; URM1, ubiquitin related modifier 1; USP5, ubiquitin specific peptidase 5; USP13, ubiquitin specific peptidase 13; VPS13D, vacuolar protein sorting 13 homolog D.